Keefektifan Penggunaan Media Audio Visual Youtube Musik Pop Dalam Pembelajaran Menulis Puisi Kelas X di SMK Islam Manbaul Hikmah - Nur Khalimah; Ghufroni Ghufroni; Hany Uswatun Nisa (Peneliti.net, 2022)
media is a tool or form of stimulus that serves to convey learning messages. In addition, the media must also stimulate students to remember what has been learned in addition to providing learning stimuli with a new atmosphere. In the learning process at school there are several fields of science that are presented to students, all of which are aimed at making students master knowledge and skills that will later benefit themselves and can compete with the existing world of work. This study aims to describe the results of the effectiveness of the use of audio-visual media youtube pop music in learning to write poetry class X SMK Islam Manbaul Hikmah on learning to write poetry. The population and samples in this study were conducted in class X of SMK Islam Manbaul Hikmah. This research uses quasi experimental design method. Keywords: Effectiveness, Learning Media, Writing poetry